2010
DOI: 10.1159/000279767
|View full text |Cite
|
Sign up to set email alerts
|

Non-Injection Drug Use Patterns and History of Injection among Street Youth

Abstract: Aims: Efforts to prevent youth from initiating injection drug use require an understanding of the drug use patterns that predispose to injecting. Here we identify such patterns and describe the circumstances of first injection among street youth. Methods: From October 2005 to November 2007, data were collected for the At Risk Youth Study, a prospective cohort of 560 street-recruited youth aged 14–26 in Vancouver, Canada. Non-injection drug use behaviors were compared between those with and without a history of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 70 publications
1
27
0
Order By: Relevance
“…In total, 87% of the oldest group respondents reported receiving an injection from another person, which is consistent with earlier findings for long-term drug users in France (Vidal-Trecan et al, 2002). In recent studies, the percentage of individuals performing the first injection alone ranged from 8% to 26% (Goldsamt et al, 2010;Hadland et al, 2010;Lankenau et al, 2010;Novelli et al, 2005). One must consider the deep social transformations in France to understand these new patterns of initiation into injection.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In total, 87% of the oldest group respondents reported receiving an injection from another person, which is consistent with earlier findings for long-term drug users in France (Vidal-Trecan et al, 2002). In recent studies, the percentage of individuals performing the first injection alone ranged from 8% to 26% (Goldsamt et al, 2010;Hadland et al, 2010;Lankenau et al, 2010;Novelli et al, 2005). One must consider the deep social transformations in France to understand these new patterns of initiation into injection.…”
Section: Discussionsupporting
confidence: 85%
“…Circumstances leading to injection in the new groups of injectors have not been well documented because the majority of studies have focused on the trajectory of long-term drug users, often the most marginalized, who are mainly recruited through drug dependence clinics or injection drug user networks (Crofts et al 1996;Doherty et al, 2000;Frajzyngier et al, 2007;Fuller et al, 2003;Goldsamt et al, 2010;Hadland et al, 2010;Kerr et al, 2007;Lankenau et al, 2010;Roy et al, 2003;Vidal-Trecan et al, 2002). The context of initiation for those who have injected only a few times or over a short period of time during their lifetime has been poorly described.…”
Section: Introductionmentioning
confidence: 99%
“…For example, previous research has identified risk factors associated with youth’s transitions into homelessness, including family dysfunction, experiences of abuse and trauma, various forms of exploitation, poverty, mental health crises, and a lack of culturally appropriate social welfare services [17]. Research from Vancouver, Canada, has identified how transitions into more harmful forms of illicit drug use among youth can be powerfully shaped by geographical transitions between neighbourhoods, and the social, structural and spatial processes that are embedded in particular places [1, 15]. As young people become entrenched in these scenes/milieus across time, transitions into homelessness and more harmful forms of drug use can come to seem increasingly inevitable given the constraints of their everyday lived experience.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggest that gender differences exist in the use of METH, and its behavioral and psychological effects. Reports suggest that females start using METH at a younger age, transition from recreational use to addiction more quickly, and initiate the injection METH earlier than their male counterparts (Dluzen and Liu, 2008; Hadland et al, 2010; Liu et al, 2013; Rawson et al, 2005). Drug craving was also significantly correlated with depression and anxiety measures in male METH users but not females (Hartwell et al, 2016).…”
Section: 0 Introductionmentioning
confidence: 99%